A Feasibility Study on the Establishment of It’s Coffeecial in Karuhatan, Mac Arthur Highway, Valenzuela City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
It’s Coffeecial is a coffee shop that offers variety of coffee and a doodle wall art. It also offers package deals and free use of laptop and WIFI. Coffee was chosen to be the primary product offering because it is believed to be a stress reliever and anti-depressant. The researchers conducted a survey to 100 respondents randomly chosen in People’s Park, Karuhatan, Mac Arthur Highway, Valenzuela City last September 3, 2018. The researchers used both quantitative and qualitative research. The questionnaire was composed of 10 questions, whose primary aim is to determine the acceptability of the researchers’ concept on product, price, place and promotion. The survey was distributed and retrieved directly to and from the respondents. Based on the survey, majority favor white chocolate for frappe as their drinks at 54%. The perfect “comBEANation” that the It’s Coffeecial offers with price of P400-P450 had the majority vote from the respondents at 97%. In terms of location, It’s Coffeecial in Karuhatan, Mac Arthur Highway, Valenzuela City was found to be accessible according to the respondents at 96%. Forty-eight percent of the respondents chose flyers to be the most favored promotional tool of the business. The proposed business will be classified as general partnership with initial capital of ₱5,000,000. Each partner is required to equally share ₱1,000,000. The total projected expense of the cafe is worth ₱4,705,032 and the remaining ₱294,968 will be used for the other operating expenses of the business. Also, based on the projected five-year financial statement of It’s Coffeecial, the sales can increase by 15% yearly. The researchers conclude that there is high demand in coffee and coffee shops. This product combined with the free use of laptop and WIFI is a big advantage in order to win more customers. Seeing the stiff competition in this line of business, It’s Coffeecial will have more strategic marketing activities. The researchers also recommend innovating the offerings to make it a more robust business in the future.
Keywords: coffee shop